2022
DOI: 10.3390/min12040396
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Predominance of Alicyclobacillus tolerans in Microbial Community during Bioleaching of Pentlandite-Chalcopyrite Concentrate

Abstract: Bacterial isolates assigned to the species Alicyclobacillus tolerans, which occupies an intermediate position between an organotrophic genus Alicyclobacillus and mixotrophic genus Sulfobacillus, were revealed as members of the acidophilic chemolithotrophic community during stirred-tank bioleaching of violarite–pentlandite–chalcopyrite concentrate at 40 °C. Surprisingly, this species succeeded more common iron-oxidizing community members after a series of bioleaching processes in bioreactors. The possibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…tolerans AMF was the main iron oxidiser in the bioleaching of a violarite-pentlandite-chalcopyrite concentrate highlighting the role of mixotrophs in this kind of processes. As in culture RA8-30H the Alicyclobacillus strain was accompanied, though in lesser abundances, by Acidithiobacillus species and other iron and/or sulphur oxidiser [40]. Another study showed that Al.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…tolerans AMF was the main iron oxidiser in the bioleaching of a violarite-pentlandite-chalcopyrite concentrate highlighting the role of mixotrophs in this kind of processes. As in culture RA8-30H the Alicyclobacillus strain was accompanied, though in lesser abundances, by Acidithiobacillus species and other iron and/or sulphur oxidiser [40]. Another study showed that Al.…”
Section: Resultsmentioning
confidence: 94%
“…Although different Alicyclobacillus species are frequently detected in molecular ecology surveys in highly acidic extreme environments, natural or anthropogenically generated ([18], [38]), they have rarely been isolated, and consequently studied especially at genomic level. In spite being mainly heterotrophs, in many cases Alicyclobacillus are the predominant iron oxidising species, even though they generally do it at lower rates than other mesophilic or moderate thermophilic iron oxidisers ( [40], [41]). Al.…”
Section: Resultsmentioning
confidence: 99%
“…Although different Alicyclobacillus species are frequently detected in molecular ecology surveys in highly acidic extreme environments, natural or anthropogenically generated ([ 3 , 24 ]), they have rarely been isolated and consequently studied, especially at the genomic level. In spite of being mainly heterotrophs, in many cases, Alicyclobacillus are the predominant iron-oxidising species, even though they generally oxidise at lower rates than other mesophilic or moderate thermophilic iron oxidisers ([ 45 , 46 ]). Al.…”
Section: Discussionmentioning
confidence: 99%
“…tolerans AMF was the main iron oxidiser in the bioleaching of a violarite–pentlandite–chalcopyrite concentrate, highlighting the role of mixotrophs in this kind of process. As in culture RA8-30H, the Alicyclobacillus strain was accompanied, although in lesser abundances, by Acidithiobacillus species and other iron and/or sulphur oxidisers [ 45 ]. Another study showed that Al.…”
Section: Discussionmentioning
confidence: 99%
“…These acidophilic archaea oxidize ferrous iron at low pH values in the presence of small amounts of organic material. They are commonly reported as members of acidophilic communities in sulfide ore deposits, processes of bioleaching of sulfide raw materials, and AMD [34,39,40]. The proportion of Pseudomonas spp.…”
Section: Microbial Community Structure In Different Zones Of Sibay Mi...mentioning
confidence: 99%